Study of factors influencing construction delays at rural area in Malaysia - Ramli M.Z.; Malek M.A.; Hanipah M.H.; Lin C.L.; Mahamad Sukri M.F.; Zawawi M.H.; Zainal Abidin M.Z.; Mohamad Fuad N.F.S. (Institute of Physics Publishing, 2023)
Construction equipment; Contractors; Economics; Surveys; Construction delays; Construction method; Economic growths; Importance index; Private projects; Questionnaire data; Questionnaire surveys; Rural constructions; Rural areas